Characterisation and antibiotic susceptibility pattern of bacterial isolates obtained from some shellfish sold in Lagos-West, Nigeria - Oramadike, C. E.; Olajuyigbe, O. O.; Amusan, Esak Esther; Esangbedo, R. O.; Awoyale, M. O. (Acta Aquatica: Aquatic Sciences Journal, 2024)
Shellfish are rich in essential nutrients and are widely accepted globally. The bacterial contamination, antibiotic susceptibility and heavy metal concentrations on some shellfish muscles above the tolerance permissible limit by WHO/FAO require an in-depth study. An investigative study was carried out on tiger shrimp (Penaeus monodon), pink shrimp (Penaeus notialis) and Lagoon crabs (Callinectes amnicola) obtained from Makoko fish market/landing site on their bacterial quality, antibiotic susceptibility patterns and heavy metal accumulation of bacteria isolated were carried out using standard methods. The highest Total bacterial count (2.48±0.02ï‚´107cfu/g) was observed in Lagoon crab (C. amnicola) while the lowest count (1.20±0.02ï‚´107cfu/g) was observed in tiger shrimp (P. monodon). However, the highest Total Faecal count (1.42±0.02ï‚´104cfu/g) was observed in pink shrimp (P. notialis) while the lowest count was observ ed in P. monodon (1.13±0.03ï‚´104cfu/g). The bacterial isolates were molecularly identified as (Morganella morganii and Proteus vulgaris) isolated from tiger shrimp, Lagoon crabs had (Proteus mirabilis) while pink shrimp showed (Alcaligenes faecalis). The isolates were 100% susceptible to ciprofloxacin, azithromycin and erythromycin and resistant to cefotaxime, cefuroxime, imipenem/clastatin, augmentin and nitrofurantoin. The mean heavy metals concentration was as follows zinc>iron>copper>nickel>chromium>manganese > Cadmium while Lead and cobalt were not detected in the samples. The study has shown a possible unhygienic environment indicative of the bacteria isolated, a possible environmental spread of antibiotic-resistant bacteria and a heavy metal-contaminated water body. There is a serious need for constant monitoring to lessen future health problems for humans in and around the environment.Keywords: antibiotic-resistant; contamination; Makoko